Influence of heat exchanger pinch point on the control strategy of Organic Rankine cycle (ORC). (15th September 2020) - Jin, Yunli; Gao, Naiping; Wang, Tiantian
Abstract: The pinch point of organic Rankine cycle (ORC) heat exchangers affects the thermal efficiency and total heat absorbed by the working fluid. The pinch point variation with operating condition is associated with the control mode. However, few studies pay attention to the influence of pinch point on ORC control strategy. In order to obtain the ORC control strategy adapting to pinch point, pinch point models are built and a case study of subcritical ORC applied to recover waste heat from boiler exhaust flue gas is conducted in this paper. The results show that pinch point temperature difference (PPTD) of the evaporator and the condenser are affected by evaporation temperature and parameters of heat and cold source in conventional control. When maintaining PPTDs, there appears a turning point (TP) of cooling water mass flow rate. At TP, the slight increase of mass flow rate with evaporation temperature changes into a sharp rise. The evaporation temperature where TP happens varies with the inlet temperature of both cooling water and gas. A control strategy of maintaining PPTDs is proposed and simulated. The evaporation temperature is regulated to maximize the thermal efficiency and to avoid the sharp rise of cooling water mass flow rate. Highlights: Pinch point models of organic Rankine cycle are built. Influences of operating parameter variation on pinch point are presented. Effects of conventional control strategies on pinch point variation are presented. Turning point of cooling water mass flow rate and influence factors are found. Control strategy of organic Rankine cycle adapting to pinch point is proposed.